Comparison of two treatment methods of congenital clubfoot in the orthopaedists’ opinion - Okoński, Piotr; Misztal-Okońska, Patrycja; Okoński, Marek; Książek, Piotr; Goniewicz, Mariusz (Polish Journal of Public Health, 2017)
Introduction. Clubfoot is the second most common birth defect of the lower limb. In Europe (including Poland) it concerns about 1-2 in 1000 newborns. What is characteristic for a clubfoot, is change in the foot shape and its impairment with preserving anatomical structures. Aim. The aim of this work is to gather opinions of orthopedic physicians on the effectiveness of the two methods used to treat congenital clubfoot: the Turco method and the Ponseti method. Material and methods. The research method used in the work was a diagnostic survey and research technique was the author’s questionnaire designed to gather opinions of orthopedic surgeons on the two methods of clubfoot treatment. The questionnaires were collected in the Orthopaedic Clinics in Lublin and Rzeszów, as well as during the specialization courses for orthopaedic surgeons in Lublin. Results. The most important advantages of the Ponseti method according to respondents are high clinical effectiveness (average 4.48) and short duration of hospitalization (average 4.31). While the most important disadvantages of the method is length of rehabilitation (average 2.85) and convalescence (average 2.36). Top assets of the Turco method in turn, according to respondents, are high clinical efficiency (average 2.92) and certainty of the patient’s recovery (2.74). In turn, the downsides of the Turco method according to the respondents are high invasiveness (average 4.11) and length of convalescence (average 3.87). Conclusion. The Ponseti method is the surveyed doctors’ preferred method of congenital clubfoot treatment.